Investigating the Social Network Structure of Physical Literacy Scholars to Advance a Paradigm for Physical Activity Promotion - Lower-Hoppe, Leeann M.; Kim, Amy Chan Hyung; Brgoch, Shea M.; Zwolski, Christin M.; Schmitt, Laura; Paponetti, Matthew K.; Quatman-Yates, Catherine C. (Frontiers in Sports and Active Living, 2022)
Purpose Physical literacy has quickly gained global attention as a holistic approach to combat physical inactivity and obesity. However, research silos may limit the growth and application of the physical literacy paradigm for effective physical activity promotion. The purpose of this study was to measure the underlying network structure of scholars publishing on physical literacy (focusing on empirical research) through co-authorship analysis. Methods Data collection resulted in 1,070 documents related to physical literacy retrieved. A total of 198 articles met inclusion criteria and were included in the full network, with authors operationalized as actors in the network. A total of 75 empirical studies were included in the sub-network for critical appraisal and further analysis. Social network analysis was then conducted at the macro- and component-level, using quantification and visualization techniques. Results Results revealed a collaborative, yet fragmented physical literacy network with sub-groups representing substantive and geographically diverse scholars. The majority of scholarship lacked empirical evidence, suggesting a research-practice gap. Conclusion Recommendations for advancing physical literacy research and practice include strategic collaborations that transcend geographic and disciplinary boundaries, cooperative efforts across scholars and practitioners, and productive discourse through professional avenues to progress knowledge generation, dispersion, and application.